Kajian Strategi Pengembangan Alun-Alun Kota Surabaya dalam Perspektif Ruang Publik - Farah Diba Azulfa; Singgih Manggalou (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to identify and analyze the development strategies of Surabaya City Square from a public space perspective. This study uses a descriptive qualitative method with a focus on the role of the Surabaya City Government, particularly the Surabaya City Culture, Youth, Sports, and Tourism Office. The analysis was conducted using Geoff Mulgan's (2009) public strategy theory, which covers five dimensions: purposes, environment, direction, action, and learning. The results show that the development strategy for Surabaya City Square has clear objectives, namely to provide an inclusive, multifunctional, and sustainable public space, as well as to integrate cultural heritage preservation with the strengthening of the city's identity. The strategic physical and social environment supports development, although there are still challenges such as limited parking space and suboptimal use of the food court. Strategic direction has been carried out through policies outlined in Local Regulation No. 3 of 2025 and technical implementation by the Technical Implementation Unit for Museum and Cultural Arts Building Management. Concrete actions in the form of cultural, educational, and creative economy programs have created an active and participatory public space. The evaluation and learning process continues through community feedback, which is used as a basis for continuous improvement. Thus, the development strategy for Surabaya City Square reflects a systematic effort to create a public space that is socially, culturally, economically, and environmentally relevant.